Effect of Dribbling Training Method on Shooting Ability Football Games for Extracurricular Students at SMAN 03 Bengkulu City - Defliyanto Defliyanto; Dian Pujianto; Bayu Insanistyo; Tono Sugihartono; Syafrial Syafrial; Bogy Restu Ilahi; Widi Kurniawan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Extracurricular students of SMAN 03 Bengkulu City. This type of research uses a pre-experimental research design which is a development method from true experimental. This design does not have a control group. This study aims to determine whether there is an influence between the independent variables on the dependent variable, the population in this study is students who take extracurricular soccer, totaling 30 students and the sample used is total sampling of the entire population of the study. The data collection technique in this study used a shooting at the ball test, namely a test of kicking the ball from a certain place and with a certain foot with a predetermined target. correlational test, the result = 0.98. Thus the contribution of Dribbling practice to shooting ability is 96.04%, after that, hypothesis testing is carried out using the t-test as follows: The hypothesis shows that t count is greater than t table. It means that there is a significant effect of Dribbling practice on Shooting ability.